Psychological Impact of Virtual Reality Gaming on the Formation of Self-Image in Early School-Age Children - Pakhomova V.G (Moscow State University of Psychology and Education, 2017)
The article investigates the problem of interaction between a modern primary school-aged child and the field of virtual reality gaming and, in particular, the impact of virtual reality on the formation of self-image. Our study enabled us to explore the differences in the self-image in active and non-active players of roleplaying video games. The outcomes proved that there are certain changes in the self-image of active players related to their self-identification with characters of computer games according to their individual psychological features, whereas for children who engage in non-role-playing games such identification is not common. It was found that non-active children players generally have positive selfacceptance and do not suffer from feelings of anxiety and abandonment; active players, on the opposite, often demonstrate inadequate self-esteem, anxiety and a tendency to self-actualise in virtual reality gaming.